STRATEGI MANAJEMEN KEUANGAN BUMD UNTUK PERTUMBUHAN EKONOMI REGIONAL DAN DAYA SAING NASIONAL - Asy’ari, Qaiyim; Ramin, Moh. (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to analyze the financial management strategies implemented by Regional-Owned Enterprises (BUMD) to enhance regional economic growth and strengthen national competitiveness. Using a descriptive qualitative approach, data were collected through in-depth interviews with leaders and financial managers of selected BUMDs in East Java. The results show that most BUMDs have adopted financial strategies based on efficiency, asset optimization, and corporate governance improvement. Key strategies identified include performance-based budgeting, revenue diversification through partnerships with the private sector, and strengthening of internal control systems. These strategies have proven effective in improving BUMD operational performance and significantly contributing to local government revenue (PAD). The findings support strategic financial management theory that emphasizes accountability, efficiency, and innovation in the public sector. The study implies the need for stronger local government policy support and enhanced human resource capacity in financial management to address increasingly complex economic challenges.